2014
DOI: 10.1007/s12029-014-9667-y
|View full text |Cite
|
Sign up to set email alerts
|

CNS Involvement in Pancreatic Adenocarcinoma: a Report of Eight Cases from the Johns Hopkins Hospital and Review of Literature

Abstract: Purpose CNS metastasis of pancreatic cancer is extremely rare, although systemic metastasis is very common. We present eight such cases with various forms of nervous system involvement. Methods Data was gathered from chart review of 800 patients with pancreatic cancer treated between 2004 and 2012 of which eight patients are described with CNS metastases. Results The median age of patients was 61.5 years and the median time to develop CNS metastasis was 29 months. Interestingly, two patients had no other s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 15 publications
5
19
0
Order By: Relevance
“…18 Cerebral metastases of pancreatic carcinoma, in contrast, are rather rare but still documented in the literature. 47 Lastly, the movie 50/50 27 portrays a tumor of the lumbar spine, a schwannoma. Like the astrocytoma in the movie Phenomenon, 26 the protagonist also benefits from his condition in an unrealistic way, freeing himself from his unhappy relationship.…”
Section: Neuro-oncologymentioning
confidence: 99%
“…18 Cerebral metastases of pancreatic carcinoma, in contrast, are rather rare but still documented in the literature. 47 Lastly, the movie 50/50 27 portrays a tumor of the lumbar spine, a schwannoma. Like the astrocytoma in the movie Phenomenon, 26 the protagonist also benefits from his condition in an unrealistic way, freeing himself from his unhappy relationship.…”
Section: Neuro-oncologymentioning
confidence: 99%
“…The same was true for serum hemoglobin. Other reports have also suggested that patients with gastric or pancreatic cancer constitute a minority of GI cancer patients who develop brain metastases [20,21]. Thirty-one percent of the patients analyzed by Sperduto et al [1] had KPS 90-100, compared to only 23% of our patients.…”
Section: Discussionmentioning
confidence: 45%
“…Treatment modalities for cranial pathology include resection followed by radiation, resection alone, or WBRT 2. Lemke et al recommend resection of metastatic lesions of pancreatic adenocarcinomas as a treatment strategy or potentially as a cure 6.…”
Section: Discussionmentioning
confidence: 99%
“…However, spread of disease to the brain is exceedingly rare and has an incidence of 0.33%–0.57% in antemortem cases as compared with 7.9% in postmortem diagnoses 2. This may be due to the short life expectancy which limits time for manifestation of neurological symptoms.…”
Section: Introductionmentioning
confidence: 99%